Blast furnace slags as functional fillers on rheological, thermal, and mechanical behavior of thermoplastics. Issue 8 (30th October 2015) - Mostafa, Abdelhamid; Laske, Stephan; Pacher, Gernot; Holzer, Clemens; Flachberger, Helmut; Krischey, Elke; Fritz, Bertram
ABSTRACT: Blast furnace slags (BFS) is a secondary byproduct of iron industry, which has a combination of acidic and basic oxides and show a complex, multiphase structure. If appropriately tailored, BFS could be an effective functional filler, improving the property profile of thermoplastics such as polypropylene (PP) and polystyrene (PS). As a raw material, the proposed filler may introduce both economic and ecological advantages, as it is considered an inexpensive secondary product rather than a natural resource. The current study aims at investigating the effect of incorporating BFS as a micro‐sized filler on the rheological, thermal, and mechanical behavior of PP and PS. BFS types in this study are air‐cooled, crystalline, and amorphous, grounded types. Both types are ground into 71, 40, and 20 μm batches and introduced in 10, 20, and 30 weight fractions via melt kneading. Mixtures are then formed into 4‐mm and 2‐mm thick plates via compression molding. Slight increase in rheological factors is observed with increasing filler loading. BFS hinders the crystallization of PP, resulting in slight increase of crystallization temperatures ( T c ) and lowering of crystallization enthalpy (Δ H c ). No significant effect of filler on transition temperatures ( T g ) is reported. Mechanically, BFS increases the tensile modulus of PP, but decreases its strength. For PS formulations, a modest toughening effect is observed by slag filler. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43021. Abstract :